MANAJEMEN MUTU TERPADU DALAM KONTEKS REGULASI DAN STANDAR INTERNASIONAL: ANALISIS DAN IMPLIKASI - Afif Syaiful Mustofa; Ahmad Ridani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in the context of international regulations and standards and its implications for organizational performance. The study employs a qualitative approach using a library research method through a systematic review of reputable scientific literature. The findings indicate that TQM has a direct effect on organizational performance and an indirect effect mediated by risk-based thinking, which enhances the organization’s ability to manage risks and uncertainties. In addition, contextual factors such as organizational readiness, institutional pressure, and sector characteristics act as moderating variables influencing the strength of these relationships. The integration of TQM with international standards such as ISO 9001 strengthens organizational legitimacy, consistency, and global competitiveness. This study proposes an integrative conceptual model explaining the multidimensional relationship between TQM, international regulations, and organizational performance. The findings contribute theoretically and provide practical implications for developing more adaptive and effective quality management systems.